Association between biochemical cartilage markers and clinical symptoms in patients with hip osteoarthritis: cohort study with 2-year follow-up. Issue 1 (January 2015) - Dorleijn, D.M.J.; Luijsterburg, P.A.J.; Bay-Jensen, A.C.; Siebuhr, A.S.; Karsdal, M.A.; Rozendaal, R.M.; Bos, P.K.; Bierma-Zeinstra, S.M.A.
Summary: Objectives: To assess associations between uCTX-II or uCIIM and severity of hip pain in patients with mild-moderate hip osteoarthritis (OA) over a 2-year period, and establish whether the level of these biomarkers at baseline could estimate a specific trajectory of hip pain. Design: A cohort study with a 2-year follow-up and 6-monthly measurements of urinary biomarkers (uCTX-II and uCIIM) and symptom severity. Patients were recruited from general practices. The primary outcome was hip pain, measured with the Western Ontario and McMasters University Osteoarthritis Index (WOMAC) subscale and the Visual Analog Scale (VAS). Associations between hip pain and biomarkers were assessed using linear mixed-model analysis for repeated measurements. Five previously identified pain trajectories were used as outcome to investigate whether the level of biomarkers at baseline could estimate membership in one of the trajectories using multinomial regression analysis. Results: LoguCTX-II and loguCIIM were not associated with WOMAC pain or VAS pain during the 2-year follow-up. Patients in the highly progressive pain trajectory and the moderate pain trajectory were more likely to have a higher loguCTX-II at baseline (OR 6.7; 95% CI 1.6–28.2 and OR 4.8; 95% CI 1.0–22.8, respectively) than patients in the mild pain trajectory. Conclusion: This study shows that in patients with mild-moderate hip OA the urinary biochemical markers uCTX-II and uCIIM are not cross-sectionally associated with hip pain during the 2-year follow-up. Because the uCTX-II level estimated a progressive or moderate hip pain trajectory, this correlation needs to be confirmed in additional patients with hip OA.